Choreography of Pelangi Surabaya Dance by Pujianti Catur Siwi - Naila Sabrina Syah,; Sekti, Retnayu Prasetyanti (Solah, 2025)
Pelangi Surabaya dance is a dance work created by Pujianti Catur Siwi in 2018 at the Surabaya City Dance Creation Festival. The beauty of the Dancing Fountain tourist attraction became the symbolic inspiration behind the creation of this dance. Pelangi Surabaya dance is composed of supporting elements such as movement, dance music, makeup, costume design, and properties. This study aims to describe the choreography of Pelangi Surabaya dance. The problem is analyzed using choreography and representation theory approaches, employing qualitative research methods. The selected object is the choreography, with data collection techniques including observation, interviews, documentation, and data analysis through the stages of reduction, data presentation, and data validity using source, technique, and time triangulation. The research results indicate that in the choreographic structure of Pelangi Surabaya dance, in addition to meeting the aesthetic requirements and artistic principles, the choreographer must also consider dance elements such as theme, title, movement, makeup, costume, and accompaniment.